New combinations in the genus Siler (Apiaceae) for the Italian Flora - Iamonico, Duilio; Bartolucci, Fabrizio; Conti, Fabio (Phytotaxa, 2016)
On the basis of nrDNA ITS sequences and plastid markers (rps16 intron, rpoC1 intron and rpoB-trnC intergenic spacer), Banasiak et al. (2016) reconstructed the phylogeny of all the genera belonging to the subtribe Daucinae Dumortier (1827: 81), showing that the former tribe Laserpitieae Bentham in Bentham & Hooker (1867: 872) constitutes a paraphyletic grade at the base of the spiny-fruited members of Daucinae, while the traditionally delimited genera Daucus Linnaeus (1753: 242) and Laserpitium Linnaeus (1753: 248) are polyphyletic. The same authors proposed to maintain Daucus as monophyletic synonymizing several names at genus level, while Laserpitium was splitted into 5 genera—Laserpitium s.str. (now including only 6 species), Ekimia Duman & Watson (1999: 200), Laser Borkhausen ex Gaertner, Meyer & Scherbius (1799: 244, 384), Siler Miller (1754: without pagination), Silphiodaucus (Koso-Poljansky 1916: 211) Spalik, Wojewódska, Banasiak, Piwczyński & Reduron in Banasiak et al. (2016: 578), and Thapsia Linnaeus (1753: 261)—and nomenclatural changes were proposed (Banasiak et al. 2016).